2016
DOI: 10.4172/2471-2698.1000114
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cefuroxime Axetil and Cefixime Trihydrate in Pharmaceutical Dosage Forms by RP-HPLC Method

Abstract: A High Performance liquid chromatographic method was developed for the determination of Cephalosporins like as: Cefuroxime axetil, Cefixime trihydrate, in pharmaceutical dosage forms. Isocratic separation was performed on an Enable C18 column (250 mm x 4.6 mm, 5.0µm) using Triethylamine: Methanol: Acetonitrile: Ultra Pure Water (2: 10: 20: 68 v/v%) as the mobile phase at a flow rate of 1.0 ml/min. The PDA detection wavelength was set at 265nm. The linearity was observed over a concentration range of 0.1-80 µg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…[2,3]. CFX is thought to be used for drug resistant bacteria [4]. Due to the frequent prescribing of CFX, it is necessitated to analyze from dosage form and from biological fluids as well.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3]. CFX is thought to be used for drug resistant bacteria [4]. Due to the frequent prescribing of CFX, it is necessitated to analyze from dosage form and from biological fluids as well.…”
Section: Introductionmentioning
confidence: 99%
“…Recent and comparative literature studies have been described for assay of CFX such as HPTLC, [ 9,10 ] spectrophotometry, [ 11–14 ] RP‐HPLC, [ 15,16 ] HPLC–MS, [ 8 ] HPLC‐UV, [ 17 ] and electrocatalytic oxidation. [ 18 ] An LC–MS/MS technique has been reported that quantifies CFX in human plasma utilizing cefetamet as the internal standard.…”
Section: Introductionmentioning
confidence: 99%
“…Various spectrophotometric [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], High Performance Liquid Chromatographic (HPLC), Reversed-phase high performance liquid chromatography (RP-HPLC), high performance thin layer chromatographic (HPTLC), micellar liquid chromatographic (MLC) [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and voltammetric [38,39] methods have been reported for the determination of cefuroxime.…”
Section: Introductionmentioning
confidence: 99%